Silk fibers and silk‐producing organs of Harpactea rubicunda (C. L. Koch 1838) (Araneae, Dysderidae). Issue 1 (4th October 2012) - Hajer, Jaromír; Malý, Jan; Řeháková, Dana
Abstract Scanning electron microscopy and atomic force microscopy were used to study the silk spinning apparatus and silks of Harpactea rubicunda spiders. Three types of silk secretions that are produced by three kinds of silk spinning glands (ampullate, piriform, and pseudaciniform) and released through three types of spigots, were confirmed for both adult and juvenile spiders. Silk secretions for the construction of spider webs for shelter or retreat are produced by the pseudaciniform silk glands. Silk secretions that are released from spigots in the course of web construction are not processed by the legs during the subsequent process of hardening. Pairs of nanofibril bundles seemed to be part of the basic microarchitecture of the web silk fibers as revealed by AFM. These fiber bundles frequently not only overlap one another, but occasionally also interweave. This structural variability may strengthen the spider web. High‐resolution AFM scans of individual nanofibrils show a distinctly segmented nanostructure. Each globular segment is ∼30–40 nm long along the longitudinal axis of the fiber, and resembles a nanosegment of artificial fibroin described by Perez‐Rigueiro et al. (2007). Microsc. Res. Tech., 2013. © 2012 Wiley Periodicals, Inc.